IMPLEMENTASI PROGRAM BAURAN PEMASARAN DAN PENGARUHNYATERHADAP KEPUTUSAN MENJADI MAHASISWA - Agus Suyatno; Wiyadi Wiyadi (Jurnal Manajemen Dayasaing, 2014)
The purpose of this study is 1 ) to describe the implementation of the marketing mix program STMIK Surakarta.2 Nations Ambassador ) to analyze the effect of marketing mix program STMIK Nations Ambassador Surakarta against interest in. SMA.3 for graduate students ) to analyze the most dominant variables affect the interestof incoming graduate students SMA to STMIK Nations Ambassador Surakarta. The analysis showed that the variables that signiﬁ cantly affect the decision making of students entering in STMIK Nations Ambassador is a product, location, promotion, personnel and process. Moderate variables did not signiﬁ cantly in the decisionmaking of students is the price and physical condition. In this study, there are still shortcomings that need to be reviewed, so that further research can be expected to complement or even enhance the research that has been done before.